On Possible Reduction of Equilibrium Radius of a Neutron Star Influenced by Superstrong Magnetic Field - Vladimir V. Skobelev (Advances in High Energy Physics)
Necessary condition for β -decay suppression of a neutron in degenerate magnetized electron gas is formulated. Based on this, it is shown that, in superstrong magnetic field, equilibrium radius of a neutron star is approximately several times smaller than without the field influence. Therefore, we can make a prediction that in short-period pulsars, such fields can be observed. In fact, possible existence of new class of stellar objects is noted, the objects with superstrong magnetic field and supersmall radius about 1 km which we named minimagnetars. They can be detected by gravitational red shift of their radiation.